Illegal Working, Migrants and Labour Exploitation in the UK. (28th August 2018) - Fudge, Judy
Abstract: The UK's Immigration Act 2016 is an assemblage of carceral elements targeting illegal working by migrants and their employers, and regulatory elements designed to enforce labour market regulation. This combination of immigration, criminal and labour law raises questions about how the UK government has framed the issue of labour exploitation. This article adopts a sociolegal approach in order to appreciate how making 'illegal working' a crime features in a specific governance project. Situating the Immigration Act 2016 within the context of neo-liberal globalisation, it develops a productive account of migrant illegality to which it adds a conception of liminal legality that emphasises both the agency of actors and the gap between legality and legitimacy. Using official documents, it shows how the Immigration Act 2016 is a response to a specific governance crisis, which is how to maintain the 'British way' of light touch labour market regulation in the face of deteriorating outcomes for many workers.